Income Diversification among Small-Holder Farmers in Bosso Local Government Area of Niger State, Nigeria - Muhammed, Y.; Adejoh, S.O; Arowolo, K.O; Galadima, C (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
The study examined income diversification among smallholder farmers in Bosso Local Government Area of Niger state, Nigeria. A multi-stage sampling technique was used to select 94 respondents for the study. Primary data were used and collected with aid of structured questionnaire complemented with an interview schedule. Descriptive statistics, diversity index and Logit regression model were employed to analyze the data collected. From the result of analysis, the mean age of the farmers was 44 years, average household size was 8 members per household and farm size was 2.4 hectares. Majority (78.7%) of the respondents acquired one form of formal education or the other, while 21.3% did not have formal education. Reasons for income diversification were poor crop and animal yield (97.9%), availability of off-farm opportunities and limited income from animal production (78.7%), and limited income from crop production (75.5%) ranked 1st, 2nd and 4th, respectively. The result further revealed that 69.2% of the respondents had an income diversity index of 0.21 - 0.40 indicating that level of income diversification was moderately low. The determinants of income diversification in the study area were age (-2.12), household size (1.83), land ownership (2.36), non – farm opportunities (5.42) and farm size (-2.47). These variables were positively related to income diversification and statistically significant 10%, 5% and 1% level of probability, respectively. In conclusion, diversification into various income sources have helped the respondents to sustain family demands, although, level of income diversification was low. It was therefore recommended that Government should formulate and implement policies that encourage smallholders to diversify their income in the study area.